2017
DOI: 10.1038/ncomms16107
|View full text |Cite
|
Sign up to set email alerts
|

Effect of water activity on rates of serpentinization of olivine

Abstract: The hydrothermal alteration of mantle rocks (referred to as serpentinization) occurs in submarine environments extending from mid-ocean ridges to subduction zones. Serpentinization affects the physical and chemical properties of oceanic lithosphere, represents one of the major mechanisms driving mass exchange between the mantle and the Earth’s surface, and is central to current origin of life hypotheses as well as the search for microbial life on the icy moons of Jupiter and Saturn. In spite of increasing inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
97
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(120 citation statements)
references
References 59 publications
(80 reference statements)
3
97
6
Order By: Relevance
“…For near‐surface serpentinization of olivine it is observed that Ω∼10 7 (Kelemen & Hirth, ), which is large due to the fact that olivine is very far out of equilibrium with water under these conditions. Using the fact that the affinity A =−Δ r G , we may write ARsT=lnnormalΩlnfalse(107false). Experimentally derived rates of serpentinization in the literature are highly variable (Lafay et al, ; Lamadrid et al, ; Malvoisin et al, ; Martin & Fyfe, ; McCollom et al, ; Ogasawara et al, ; Wegner & Ernst, ) and temperature dependent. Rates in the aforementioned studies range from 10 −10 to 10 −7 mol·m −2 ·s −1 for temperatures in the range of 200–400 °C.…”
Section: Model Setupmentioning
confidence: 99%
See 2 more Smart Citations
“…For near‐surface serpentinization of olivine it is observed that Ω∼10 7 (Kelemen & Hirth, ), which is large due to the fact that olivine is very far out of equilibrium with water under these conditions. Using the fact that the affinity A =−Δ r G , we may write ARsT=lnnormalΩlnfalse(107false). Experimentally derived rates of serpentinization in the literature are highly variable (Lafay et al, ; Lamadrid et al, ; Malvoisin et al, ; Martin & Fyfe, ; McCollom et al, ; Ogasawara et al, ; Wegner & Ernst, ) and temperature dependent. Rates in the aforementioned studies range from 10 −10 to 10 −7 mol·m −2 ·s −1 for temperatures in the range of 200–400 °C.…”
Section: Model Setupmentioning
confidence: 99%
“…Fitted serpentinization rates as function of temperature suggest that these rates may decrease by ∼1–4 orders of magnitude for temperatures in the range of 50–150 °C (Kelemen & Matter, ). Moreover, recent experiments by Lamadrid et al () show that the rate of serpentinization is heavily influenced by fluid salinity. Given the large uncertainty it seems reasonable that r will vary by several orders of magnitude.…”
Section: Model Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…We focus on seawater that has interacted chemically with 7-10 km of oceanic crust on its way to the oceanic Moho. Serpentinization at this depth would proceed with higher water and silica activity than typical for a metamorphic system supplied by local mineral dehydration (Klein et al, 2015;Lamadrid et al, 2017) but far lower water activity than typical for laboratory experiments (Klein et al, 2009;McCollom et al, 2016;Ueda et al, 2017). In order for the output of this system to be the diffuse, salinity-elevated, sulfide-free, Fe 2+ -rich fluid consumed by Zetaproteobacteria on the deep flanks of volcanic systems oceanwide (Bach, 2016;Johannessen et al, 2017), multiple metasomatic reactions should effect a net exchange of alkali cations Na + , and perhaps K + , with ferrous cation Fe 2+ .…”
Section: 1029/2019gc008493mentioning
confidence: 99%
“…Serpentinization consumes H 2 O, which raises the salinity of the metasomatic fluid. Increased Cl − impedes the serpentinization reaction (Lamadrid et al, 2017) and strips Fe from the peridotite in both its oxidation states, for example, in solid ferric iowaite (Mg 4 Fe(OH) 8 OCl-4H 2 O) (Sharp & Barnes, 2004) and ferrous chloride (FeCl 2 ) in solution (Syverson et al, 2017). Sharp and Barnes (2004) find considerable Cl incorporated in abyssal serpentinites, partially in soluble salts at mineral-grain boundaries.…”
Section: 1029/2019gc008493mentioning
confidence: 99%